92.4k views
3 votes
This equation has one solution.

5(x-1) + 3x = 7x + 1)
What is the solution?
Help now

2 Answers

1 vote

Answer:

x=12

Explanation:

5x - 5 + 3x = 7x + 7

8x - 5 = 7x + 7 ( subtract 7x from both sides )

x - 5 = 7 ( add 5 to both sides )

x = 12

User Elon
by
4.9k points
4 votes

Answer:

x=6

Explanation:

5(x-1) + 3x = 7x + 1

Distribute

5x -5 +3x = 7x+1

Combine like terms

8x -5 = 7x+1

Subtract 7x from each side

8x- 7x -5 = 7x-7x+1

x-5 =1

Add 5 to each side

x-5+5 = 1+5

x=6

User Christian Bekker
by
6.1k points